A Toolkit to Assess the Consistency Between Real Sector and Financial Sector Forecasts - Chen, Sophia; Ganum, Paola; Rabanal, Pau. (Washington, D.C. : International Monetary Fund, 2017)
e develop a toolkit to assess the consistency between real sector and financial sector forecasts. The toolkit draws upon empirical regularities on real sector and financial sector outcomes for 182 economies from 1980 to 2015. We show that credit growth is positively correlated with real sector performance, in particular when credit growth is unusually high or low. However, the relationship between credit growth and inflation is weak. These results hold for different country groups, including advanced economies, emerging markets and low-income countries. Combining credit growth with other variables such as house prices and the output gap helps to understand real sector outcomes. But including the financial account balance does not make a difference.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet